Pengaruh Kualitas Laba Terhadap Nilai Perusahaan Dengan Variabel Moderasi Corporate Governance - Richard Jannuar Ade Irawan Wairisal; Hariyati Hariyati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
This study aims to analyze the effect of earnings quality on firm value with corporate governance as the moderating variable. Industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2019 are used as population in this study. The sample selection used a purposive sampling technique by determining certain criteria which resulted in 103 companies as the sample. This study uses printed documentation of annual reports and a matrix as research instruments. This study uses the Structural Equation Model (SEM) hypothesis testing supported by the Partial Least Square (PLS) analysis method. The results of this study are that the quality of earnings has a positive effect on firm value and the moderating variable of corporate governance can strengthen the effect of earnings quality on firm value.